More than carved stone: applying a landscape narrative to commemorate the legacy of Dr. Martin Luther King Jr. - Pasowicz, Grant T. (Kansas State University, 2021)
The purpose of a memorial is to help the living remember specific events, entities, people, or places (Beamish 2020). With an increase in the number of memorials, there is a danger that the impact of memorials can be diminished (Tokin and Laurence 2003). Memorials often use an "object-based approach" to memorialize the subject; however, objects, such as statues, fountains, and plaques, alone may not create a meaningful connection to the subject, nor tell a worthwhile story. Yet, stories are useful in helping internalize information (Short 2012). For a memorial to be meaningful, the story the design tells should be grounded in a shared social or cultural understanding that resonates across generations and cultures. In memorial design, a landscape narrative can be used to tell a story with landscape elements, like topography, water, pathways, and trees, and with the use narrative practices, including naming, sequencing, revealing and concealing, gathering, and opening (Potteiger and Purinton 1998). This project commemorates the legacy of Dr. Martin Luther King, Jr. (MLK), and his work during the civil rights movement, in the projective design of a memorial space at Martin Luther King Jr. Square Park in Kansas City, Missouri. A landscape narrative was used to inspire and inform the design of the memorial space. The selected story focused on MLK’s core values of altruism, morality, and determination. These values were derived from an in-depth historical document analysis. Other methods included a site analysis, to understand the opportunities and constraints of the park site, and a precedent study, to understand how landscape narratives are used in notable memorial sites. The resulting memorial design included an amphitheater, a reflective garden, a wall engraved with historical imagery, and several other designed features that provide the community a welcoming place to gather, reflect, and learn about MLK and the civil rights movement.
Keywords: Martin Luther King, Jr.; Memorial; Kansas City; Landscape; Narrative